2014
DOI: 10.1037/a0033745
|View full text |Cite
|
Sign up to set email alerts
|

Locus of semantic interference in picture naming: Evidence from dual-task performance.

Abstract: Disagreement exists regarding the functional locus of semantic interference of distractor words in picture naming. This effect is a cornerstone of modern psycholinguistic models of word production, which assume that it arises in lexical response-selection. However, recent evidence from studies of dual-task performance suggests a locus in perceptual or conceptual processing, prior to lexical response-selection. In these studies, participants manually responded to a tone and named a picture while ignoring a writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
95
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(118 citation statements)
references
References 79 publications
(416 reference statements)
21
95
2
Order By: Relevance
“…That is, the magnitude of the semantic interference effect should not differ between short and long SOAs. This is what Schnur and Martin (2012) and Piai et al (2013a) observed. The utility of the active scheduling account of dual-task performance was demonstrated in computer simulations with the WEAVER++ model of word planning (e.g., Levelt et al, 1999;Roelofs, 1992Roelofs, , 2003 extended by assumptions about active scheduling from Kieras (1997a, 1997b).…”
Section: Passive Queuing and Active Scheduling Accountssupporting
confidence: 76%
See 4 more Smart Citations
“…That is, the magnitude of the semantic interference effect should not differ between short and long SOAs. This is what Schnur and Martin (2012) and Piai et al (2013a) observed. The utility of the active scheduling account of dual-task performance was demonstrated in computer simulations with the WEAVER++ model of word planning (e.g., Levelt et al, 1999;Roelofs, 1992Roelofs, , 2003 extended by assumptions about active scheduling from Kieras (1997a, 1997b).…”
Section: Passive Queuing and Active Scheduling Accountssupporting
confidence: 76%
“…Given our earlier results (Piai et al, 2013a), we expected not only to find the Stroop-like effect to be additive with SOA (replicating Fagot and Pashler), but also to obtain additive effects of semantic relatedness and SOA (replicating our earlier findings and those of Schnur & Martin, 2012).…”
Section: The Present Studysupporting
confidence: 64%
See 3 more Smart Citations